Location Based Work Reminder - Prabhavathi.M, Rajabharathi.C, Preethi.B (International Journal of Modern Agriculture, 2021)
The project entitled as â€œLOCATION BASED WORK REMAINDERâ€ is one of the android application. In an existing system the user sets an alarm in the googlemap to track the location but cannot save the work. In the proposed system, the Application used to track the location people may have different work in different places. They may forgot to keep track of all the work which is associated at different places. Where user will be reminded about his work at certain place where the work is associated with. This system tracks the user location with the help of GPS. System retrieves the userâ€™s current geological coordinates, with the help of this system tracks userâ€™s current location. User must enter the task by specifying the location name and work at particular places. User can enter the multiple tasks. After entering the task details user will get the map in which the task location will be circled and he will get know the distance between his current location and the task location. Once the user clicks the start option user will get notification as he reaches near to the location. System will continuously checks the location of the user and gives notification to the user as user reaches task location. This system helps the user to set, edit the alarms as he wishes. This system also helps to check the task location on the map how far he is from the current location. The application is built using android with Java, Android Studio 2.3.3 as Front End.